Cultural and human ecological resilience at Early Bronze Age bat - Swerida, Jennifer; Dollarhide, Eli N.; Fouache, Eric; Engel, Max; Beuzen-Waller, Tara; Prosperini, Aleksandre; Cosandey, Claude; Callonnec, Laurence Le; Desruelles, Stephane; Suryanarayan, Akshyeta; Buffington, Abigail; Bryant, Robert; et al. (Open Quaternary, 2024)
The Bat landscape of northwestern Oman is one of intermittent archaeological remains and varied ecological conditions. The site has been a center for human activity since the Neolithic, most famously attested by the Early Bronze Age tombs, towers, and settlement of the UNESCO World Heritage zone. This paper presents recent research conducted by the Bat Archaeological Project in reconstructing the site’s third millennium BC cultural landscape and the human-environment interactions that led to its creation and long-term occupation. Three of Bat’s Early Bronze Age environs: the Settlement Slope, al-Khutm, and Rakhat al-Madrh are discussed in view of their ecological, geomorphological, and archaeological contexts. New archaeobotanical and 14C results are presented. These discoveries suggest Bat’s ancient inhabitants sought out and utilized diverse environments in order to establish cultural and ecological resilience within a localized area. Ultimately, we propose an expansion to the traditional oasis model of settlement and agricultural development in southeast Arabia, arguing for a systems-based approach that incorporates roles played by environs beyond the oasis.